Shadows of trauma: memory and the politics of postwar identity - Assmann, Aleida (Fordham University Press, 2016)
Machine generated contents note: -- Preface to the English Language Edition -- Introduction -- Part I: Theoretical Foundations -- 1. From Individual to Collective Constructions of the Past -- 2. Basic Concepts and Themes of Individual and Collective Memory -- Part II: Analyses and Case Studies -- 3. How True are Memories? -- 4. False Memories: Pathologies of Identity at the End of the Twentieth Century -- 5. Incorrect Memories: On the Normative Power of Social Frameworks of Memory -- 6. Five Strategies of Represssion -- 7. German Narratives of Victimhood -- 8. Points of Intersection Between Lived Memory and Cultural Memory -- 9. Lieux de Mémoire in Time and Space -- 10. The Future of Holocaust Memory -- 11. Europe as a Memory Community -- Conclusion: Shadows of Trauma -- Notes -- Bibliography -- Index